Factors that influence demand of single storey terrace house (case study : Asam Kumbang District, Taiping, Perak) - 604606 Tan, Yew Choo, 1990- author; Hasmah Abu Zarin, supervisor; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2014